From oligomers towards a racemic crystal: molecular simulation of dl-norleucine crystal nucleation from solution. Issue 36 (3rd December 2014) - Ectors, Philipp; Duchstein, Patrick; Zahn, Dirk
Abstract : We elucidate the evolution of forming nuclei leading towards a racemic molecular crystal by means of computer simulation. Abstract : We elucidate the evolution of forming nuclei leading towards a racemic molecular crystal by means of computer simulation. Our simulations start with the association of individuald - andl -norleucine molecules and subsequent formation of aggregates and thus provide molecular scale insights into the early stages of nucleation from (octanol) solution. During aggregate evolution from micelles to bilayers and eventually nanoparticles comprising staggered bilayers we identified a step-wise increase in molecular ordering. While the key structural motifs in the early aggregates are given by hydrogen bonded dimers, after association of ~150 molecules a solid–solid phase transition leads to ordering of the hydrogen-bonded network in favour of the final crystal structure. This secondary nucleation event seems to be of key importance for changing the initially random arrangement ofd andl enantiomers in the small (<150 molecules) aggregates to an ordered arrangement, that is alternating -d-d - and -l-l -alignments within the staggered bilayers of the molecular crystal.